Kajian metabolit sekunder tanaman ginseng Korea dan Indonesia sebagai peningkat imun tubuh - Siti Azizah Ardiningtyas; Nor Isnaeni Dwi Arista (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Health is essential so viruses and diseases do not quickly attack the body's immune system. The use of plants to maintain health is a form of human relationship with the natural environment. Many medicinal plants can potentially increase the body's immunity, including Ginseng. Various ginseng species, such as Panax Ginseng, are in demand by the public because they have many benefits for preventing and treating various diseases. The active ingredients are amino acids, alkaloids, phenols, proteins, polypeptides, vitamins B1 and B2. P. ginseng roots can increase the activity of effector immune cells, cardiovascular disease, and the central nervous system. Meanwhile, the local Ginseng in Indonesia, Kolesom (Talinum triangulare (Jacq.) Willd), is called Javanese Ginseng, which is still considered a weed even though it contains many bioactive compounds that are rich in benefits. The use of medicinal plants in society was originally a form of traditional knowledge within a community group passed down from generation to generation. With science and technological knowledge increasingly developing, Ginseng has become an exciting study to continue developing and researching. Until now, traditional and modern societies still use Ginseng as a potential plant. Good knowledge from the public regarding the benefits of the ginseng plant requires scientific evidence of this medicinal plant for specific health conditions and diseases that need to be optimized and rationalized.